Guideline on the management of occupational and non-occupational exposure to the human immunodeficiency virus and recommendations for post-exposure prophylaxis: 2015 Update - Moorhouse, Michelle (South Afr J HIV Med, 2015)
This guideline is an update of the post-exposure prophylaxis (PEP) guideline published by the Southern African HIV Clinicians Society in 2008. It updates the recommendations on the use of antiretroviral medications to prevent individuals who have been exposed to a potential HIV source, via either occupational or non-occupational exposure, from becoming infected with HIV. No distinction is made between occupational or non-occupational exposure, and the guideline promotes the provision of PEP with three antiretroviral drugs if the exposure confers a significant transmission risk. The present guideline aligns with the principles of the World Health Organization PEP guidelines (2014), promoting simplification and adherence support to individuals receiving PEP.